FLORA OF BALI: A PROVISIONAL CHECKLIST - Max M. J. van Balgooy; Elizabeth Anita Widjaja (Research Center for Biology, 2014)
Compared to Java the flora of Bali is poorly known. A checklist has been prepared based on literature and collections. The focus is on indigenous species, but the distinction between indigenous and naturalized species is not always clear. This checklist is therefore very provisional. The flora of the much smaller island state Singapore is much richer, probably mainly due to undercollecting of Bali.